Synthesis and characterization of thermoluminescent glass-ceramics Li2O–Al2O3–SiO2:CeO2 (2009)
ABSTRACT: Vitroceramic powders of Li2O–Al2O3–SiO2 systems (LAS), doped with 1% (LAS:1Ce) and 10% (LAS:10Ce) molar of cerianite (CeO2) were synthesized by means of the gelification technique of metal formates of aluminum and lithium, in the presence of tetraethoxy silane and CeO2. The gels obtained were dried (120 °C, 2.5 h), calcined (480 °C, 5 h) and sinterized (1250 °C, 30 min). The sinterized samples were characterized by X-ray difraction (XRD), scanning electron microscopy (SEM) and microchemical analysis (EDS). There is evidence for a mixture of two phases of 64% β-spodumene (Li2O–Al2O3–4SiO2) and 36% β-eucryptite (Li2O–Al2O3–2SiO2). The LAS:1Ce system was enriched in aluminum, the LAS:10Ce system showed areas of heterogeneous composition; some regions with a shortage of CeO2, while others zones with cerium cumulus. From the microscopy images it was found that CeO2 acts as a densificant agent in LAS system, favoring the sintering in the host. The chemical route and the sintering processes utilized allow the production of samples exhibiting an acceptable linear correlation between total thermoluminescent emission intensity and the irradiation dose when the CeO2 concentration is low (less than 1%), opening the possibility of using this kind of glass-ceramic in dosimetry.